Complicating cure: How Australian criminal law shapes imagined post‐hepatitis C futures. Issue 1 (18th October 2022) - Seear, Kate; Mulcahy, Sean; Kagan, Dion; Lenton, Emily; Fraser, Suzanne; Valentine, Kylie; Farrugia, Adrian
Abstract: In recent years, highly tolerable and effective drugs have emerged promising a radical new 'post‐hepatitis C' world. Optimism about medical cure potentially overlooks discrimination and stigma associated with hepatitis C and injecting drug use. Legal frameworks are especially relevant to hepatitis futures, since the law has the potential to reinforce or alleviate stigma and discrimination. This article explores how hepatitis C figures in Australian criminal law and with what potential effects. Drawing on Bruno Latour's work on legal veridiction, Alison Kafer's work on futurity and disability and case law data collected for a major study on hepatitis C and post‐cure lives, we explore how the criminal law handles hepatitis C in the age of cure. We find that law complicates cure, constituting hepatitis C as disabling despite the advent of effective cures. The law steadfastly maintains its own approach to disease, disability and illness, untouched by medical and scientific developments, in ways that might complicate straightforwardly linear imaginaries of cure, transformation and progress of the kind that dominate biomedicine. We explore the implications of these tensions between law and medicine.